Reference values for lysosomal enzymes activities using dried blood spots samples - a Brazilian experience - Martins Ana M; Pereira Vanessa G; Rodrigues Mayra DB; Müller Karen B; D'Almeida Vânia (BMC, 2010)
Abstract Background Lysosomal storage diseases (LSD) are inherited disorders caused by deficiency of lysosomal enzymes in which early diagnosis is essential to provide timely treatment. This study reports interval values for the activity of lysosomal enzymes that are deficient in Mucopolysaccharidosis type I, Fabry, Gaucher and Pompe disease, using dried blood spots on filter paper (DBS) samples in a Brazilian population. Results Reference activity values were obtained from healthy volunteers samples for alpha-galactosidase A (4.57 ± 1.37 umol/L/h), beta-glucosidase (3.06 ± 0.99 umol/L/h), alpha-glucosidase (ratio: 13.19 ± 4.26; % inhibition: 70.66 ± 7.60), alpha-iduronidase (3.45 ± 1.21 umol/L/h) and beta-galactosidase (14.09 ± 4.36 umol/L/h). Conclusion Reference values of five lysosomal enzymes were determined for a Brazilian population sample. However, as our results differ from other laboratories, it highlights the importance of establishing specific reference values for each center.